2019
DOI: 10.1186/s12889-019-6682-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early sexual initiation among preparatory and high school youths in Woldia town, northeast Ethiopia: a cross-sectional study

Abstract: Background Early initiation of sexual activity affects the sexual and reproductive health of the young population. The youth are at a high risk of risky sexual behaviours, including multiple partners and inconsistent condom use. There has been limited research on the level and determinants of early sexual initiation in Woldia town. Thus, this study aimed to assess the prevalence of early sexual initiation and associated factors among preparatory and high school students in Woldia town, northeast E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 21 publications
9
64
1
7
Order By: Relevance
“…Our nding that premarital sex is more common among those students who watch pornography than those who do not is in agreement with a similar study conducted among students of Debre Berhan and Bahir Dar Universities [22,23]. The effect of watching pornography on premarital sexual practice is also evident among high school students in Ethiopia [39,40,44]. The most probable reason for higher frequency of premarital sex among pornography watchers is that watching pornography stimulates them to have sex.…”
Section: Discussionsupporting
confidence: 89%
“…Our nding that premarital sex is more common among those students who watch pornography than those who do not is in agreement with a similar study conducted among students of Debre Berhan and Bahir Dar Universities [22,23]. The effect of watching pornography on premarital sexual practice is also evident among high school students in Ethiopia [39,40,44]. The most probable reason for higher frequency of premarital sex among pornography watchers is that watching pornography stimulates them to have sex.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the likelihood of premarital sexual practice among female was higher, when compared with male counterparts. This is because the effect of culture forces females to be exposed towards premarital sex than their male counterparts and most girls have a belief that they become ready to do anything to make their love succeed [17]. In contrast to the report from this systematic review and meta-analysis, studies from Nepal and Vietnam showed male were more likely to be involved in premarital sex than female [4,6,54], because mostly men have freedom to decide on major tasks in their life.…”
Section: Associated Factors Of Premarital Sexual Practices In Ethiopiamentioning
confidence: 87%
“…The likely hood of premarital sexual practice among those individuals viewing pornography (sex lm) was 3.24 times higher than those not seen pornography with OR = 3.24, (95% CI; 1.95, 5.38) ( gure-3 and gure-4). Young age is more liberal towards their sexual behaviors [17].…”
Section: Associated Factors Of Premarital Sexual Practices In Ethiopiamentioning
confidence: 99%
See 2 more Smart Citations